Case report: necrotizing enterocolitis with a transverse colonic perforation in a 2-day old term neonate and literature review - Hudson, Jo-Anna; Byrns, Simon; Nizalik, Elizabeth; Ferretti, Emanuela (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Necrotizing enterocolitis (NEC), while classically discussed in preterm and low birth weight neonates, also occurs in the term infant and accounts for 10% of all NEC cases. Despite there being fewer reported cases of NEC in term infants, these presentations demonstrate differences in the onset, severity and risk factors from the classic presentation observed in premature infants. We present a novel case of term NEC that contravenes the reported literature making departures from clinical presentation, risk factors and location of perforation in an otherwise healthy term two-day old infant born after an uncomplicated pregnancy who presented with hematochezia. Case presentation A healthy term baby born after an uneventful pregnancy presented with bloody stool at 2 days of life who was otherwise well. Investigations revealed pneumoperitoneum from a large proximal transverse colonic perforation secondary to NEC. No typical risk factors for NEC were found. Conclusion Given the life-threatening potential of an unrecognized perforation we recommend the inclusion of NEC on the differential for neonatal hematochezia.